2010
DOI: 10.1016/j.cell.2010.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Patronin Regulates the Microtubule Network by Protecting Microtubule Minus Ends

Abstract: Tubulin assembles into microtubule polymers that have distinct plus and minus ends. Most microtubule plus ends in living cells are dynamic; the transitions between growth and shrinkage are regulated by assembly-promoting and destabilizing proteins. In contrast, minus ends are generally not dynamic, suggesting their stabilization by some unknown protein. Here, we have identified Patronin (also known as ssp4) as a protein that stabilizes microtubule minus ends in Drosophila S2 cells. In the absence of Patronin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
337
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(352 citation statements)
references
References 53 publications
(79 reference statements)
15
337
0
Order By: Relevance
“…Nezha [also known as calmodulin-regulated spectrin-associated protein 3 (CAMSAP3)] tethers noncentrosomal microtubules to the adherens junctions via its attachment to the minus ends of these microtubules (8). The Drosophila protein Patronin, which is related to CAMSAP3, stabilizes the minus ends of microtubules by protecting them against Kinesin 13-mediated depolymerization (9). Two other proteins, CAMSAP1 and CAM-SAP2, are also related to CAMSAP3 (10), but their functions remain undetermined.…”
Section: γ-Tubulin | Eb1mentioning
confidence: 99%
“…Nezha [also known as calmodulin-regulated spectrin-associated protein 3 (CAMSAP3)] tethers noncentrosomal microtubules to the adherens junctions via its attachment to the minus ends of these microtubules (8). The Drosophila protein Patronin, which is related to CAMSAP3, stabilizes the minus ends of microtubules by protecting them against Kinesin 13-mediated depolymerization (9). Two other proteins, CAMSAP1 and CAM-SAP2, are also related to CAMSAP3 (10), but their functions remain undetermined.…”
Section: γ-Tubulin | Eb1mentioning
confidence: 99%
“…It remains to be determined whether a stabilisation of interpolar microtubules that pre-exist from metaphase is sufficient for the formation of the central spindle or whether de novo microtubule polymerisation (Uehara and Goshima, 2010) is also required. The molecular details of the anchoring of the microtubule minus ends or their stabilisation without a specific anchoring structure are also unclear, although c-tubulin (Julian et al, 1993;Shu et al, 1995) and its associated proteins, such as augmin (Uehara et al, 2009) and minus-end-directed motor kinesin-14 (Cai et al, 2010), as well as the recently identified microtubule minus-end stabiliser patronin (Goodwin and Vale, 2010) have been suggested to be involved. By contrast, the roles of motors and microtubule-associated proteins (MAPs) that localise to the central anti-parallel overlaps have been better characterised as described below.…”
mentioning
confidence: 99%
“…MT minus-end binding proteins display stabilizing or protecting activities, and largely contribute to noncentrosomal MT generation. C. elegans possesses three known -TIPs (Box 1): g-tubulin and its associated proteins GIP-1 and GIP-2 (Hannak et al, 2002), PTRN-1 [belonging to the conserved Patronin/ Nehza/calmodulin and spectrin-associated family (CAMSAP) (Goodwin and Vale, 2010)], and NOCA-1(noncentrosomal array 1) with homology to ninein (Wang et al, 2015). PTRN-1 function has mostly been described in neurons (Marcette et al, 2014;Richardson et al, 2014), and axon regeneration (Chuang et al, 2014).…”
Section: Noncentrosomal Minus-end Targeting Proteins (-Tips) and Mt Dmentioning
confidence: 99%
“…They include the major MT nucleator g-tubulin/TBG-1 and its associated complex containing GIP-1 and GIP-2 (gamma-tubulin interacting protein, formerly called CeGrip-1/2, Hannak et al, 2002); -TIPs also include NOCA-1 (Wang et al, 2015) and the patronin homologue PTRN-1, formerly PQN-34 (Goodwin and Vale, 2010; see main text for details).…”
Section: Minus-end Interacting Proteins (-Tips)mentioning
confidence: 99%